2021
DOI: 10.1148/radiol.2021204106
|View full text |Cite
|
Sign up to set email alerts
|

Interval Breast Cancer Rates and Tumor Characteristics in the Prospective Population-based Malmö Breast Tomosynthesis Screening Trial

Abstract: Background: Interval cancer rates can be used to evaluate whether screening with digital breast tomosynthesis (DBT) contributes to a screening benefit. Purpose:To compare interval cancer rates and tumor characteristics in DBT screening to those in a contemporary population screened with digital mammography (DM). Materials and Methods:The prospective population-based Malmö Breast Tomosynthesis Screening Trial (MBTST) was designed to compare one-view DBT to two-view DM in breast cancer detection. The interval ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 31 publications
2
40
1
Order By: Relevance
“…24 A prospective, population-based screening trial (Malmo Breast Tomosynthesis Screening Trial) compared with a large contemporary control group screened with digital mammography showed a lower interval cancer detection rate. 25 These results are concordant with other previous published studies. 26,27 The interval cancers' characteristics (i.e., the proportion of invasive, size, grade, and nodal status) with DBT screening were similar to those identified in previous DM-only rounds.…”
Section: Interval Cancer Detection Ratesupporting
confidence: 93%
“…24 A prospective, population-based screening trial (Malmo Breast Tomosynthesis Screening Trial) compared with a large contemporary control group screened with digital mammography showed a lower interval cancer detection rate. 25 These results are concordant with other previous published studies. 26,27 The interval cancers' characteristics (i.e., the proportion of invasive, size, grade, and nodal status) with DBT screening were similar to those identified in previous DM-only rounds.…”
Section: Interval Cancer Detection Ratesupporting
confidence: 93%
“…When an increase in cancer detection at screening is observed, a decrease in interval cancer rate is anticipated. To date, among the few studies reporting interval cancer rates after screening with DBT+DM/SM, only MBTST has demonstrated a statistically significant interval cancer reduction, otherwise no statistically significant differences were observed (Table 1.6) (104,157,(159)(160)(161)(162)(163)(164)(165) . A recent meta-analysis of five European studies demonstrated a pooled difference in interval cancer rates for DBT versus DM of -0.15/1000 (95% CI -0.59 -0.29) (166).…”
Section: Dbt In Screeningmentioning
confidence: 99%
“…In contrast, most other prospective non-randomized studies were based on sequential reading of DBT and DM images from the same women (39,45,60,62,156). In the studies from Oslo (OTST) and Malmö (MBTST), four different radiologists performed screen-reading of each exam, followed by a consensus meeting including all images, a design that might potentially have increased the cancer detection as well as reduced the interval cancer rates (158,165). In the STORM studies, sequential reading was performed by the same radiologist, and women were recalled if screen-reading was positive in either step, which may also have biased the results in favor of DBT (45,62).…”
Section: Screening With Dbtmentioning
confidence: 99%
“…35 The most recent screening tomosynthesis study of a 5-year period found an ICR of 1.6 per 1000 screened women, compared with 2.8 per 1000 screened women in the control group. 74 Recalls are highest in prevalence scans for any modality, and with supplemental US, recalls reported at 15.1%, decreased to 7.4% in subsequent scans. 62 Similarly with supplemental MRI screening, there were higher recalls of 9.5% in the DENSE trial in the prevalence scans which decreased to 3.2% on incidence screening.…”
Section: Discussionmentioning
confidence: 93%